Myrciariamyia admirabilis, a new species of gall midge (Diptera, Cecidomyiidae) associated with Erythroxylum suberosum (Erythroxylaceae) - Maia, Valéria Cid; Fernandes, G. Wilson (Zootaxa, 2007)
Myrciariamyia admirabilis Maia, a new species of Cecidomyiidae (Diptera) that induces leaf galls on Erythroxylum suberosum A.St.-Hil. (Erythroxylaceae) is described and illustrated (larva, pupa, male, female and gall) based on material from Minas Gerais, Brazil.